Green leafy vegetable and lutein intake and multiple health outcomes. (30th October 2021) - Li, Ni; Wu, Xiaoting; Zhuang, Wen; Xia, Lin; Chen, Yi; Wang, Yong; Wu, Chuncheng; Rao, Zhiyong; Du, Liang; Zhao, Rui; Yi, Mengshi; Wan, Qianyi; et al.
Highlights: Umbrella review of 29 outcomes in 24 systematic reviews and meta-analyses. GLVs intake reduces all-cause mortality, CVD, cancer and other outcomes. Per 100 g/d increment decrease 25% risk of mortality, CHD and stroke. Dietary lutein intake reduces age-related eye diseases (AMD and cataract). Caution was warranted for potentially pathogenic contamination ( Escherichia coli ). Abstract: Green leafy vegetables (GLVs) are a key element of healthy eating patterns and are an important source of lutein. To clarify the evidence for associations between GLVs and lutein intake and multiple health outcomes, we performed a review. A total of 24 meta-analyses with 29 health outcomes were identified by eligibility criteria. Dose-response analyses revealed that, per 100 g/d GLV intake was associated with a decreased risk (ca. 25%) of all-cause mortality, coronary heart disease and stroke. Beneficial effects of GLV intake were found for cardiovascular disease and bladder and oral cancer. Dietary lutein intake was inversely associated with age-related macular degeneration, age-related cataracts, coronary heart disease, stroke, oesophageal cancer, non-Hodgkin lymphoma, metabolic syndrome, and amyotrophic lateral sclerosis. Caution was warranted for contamination with potentially pathogenic organisms, specifically Escherichia coli . GLV consumption and lutein intake therein are generally safe and beneficial for multiple health outcomes in humans.